Healthy mat type nursery of rice and basmati rice for successful mechanical transplanting - Kang, J S; Kaur, Jagroop; Manhas, S S; Singh, Harmeet (Indian Farming, 2025)
Rice occupies largest area among all the crops in India. Its cultivation is done on above 46 million hectares and it is grown mainly by manual transplanting method which is highly labour intensive. As the wages of labour are sky rocketing, the cost of cultivation of manual transplanted rice is also increasing at the same pace, in addition, manual transplanting is a time consuming method. Suboptimal planting density as compared with optimum planting density of 33 hill/m2 and delay in transplanting of rice with this method leads to low crop productivity. These issues can be addressed by shifting transplanting method from manual to cost-effective mechanical planting technique. Different types of rice transplanters are available which have the provision to adjust the plant to plant spacing, number of seedlings per hill and depth of transplanting. However, the large scale adoption of mechanical transplanting of rice depends on successful raising of mat type nursery which seems tedious to farmers.